Business Model Canvas - Overview of the main advantages and disadvantages - Marco Becker; Jan-Oliver Bröcker (ZBW - Leibniz Information Centre for Economics, 2021)
Over the last 10 years, the Business Model Canvas has not only established itself as a method for the iterative development and documentation of business models, it has also become a standard methodology in some areas. In this article, the main advantages and disadvantages associated with the practical application of the Business Model Canvas will be compiled and evaluated in terms of their current validity. It has been shown that some of the advantages and disadvantages documented in the relevant literature were justified at the time of their respective publication but can now no longer be considered valid. – – Das Business Model Canvas hat sich in den letzten rund 10 Jahren nicht nur einen festen Platz als Methode zur iterativen Entwicklung und Dokumentation von Geschäftsmodellen erarbeitet, sondern es hat sich auch in einigen Bereichen als Standardmethodik etabliert. In diesem Artikel sollen die wesentlichen Vor- und Nachteile, die mit der praktischen Anwendung des Business Model Canvas verbunden sind, zusammengetragen und hinsichtlich ihrer aktuellen Gültigkeit bewertet werden. Dabei hat sich gezeigt, dass sich einige der in der einschlägigen Literatur dokumentierten Vor- und Nachteile zwar zum Zeitpunkt der jeweiligen Veröffentlichung ihre Berechtigung hatten, inzwischen aber als nicht mehr stichhaltig angesehen werden können.
Keywords: M130; 330; Business Model Canvas; Advantages and Disadvantages